A case of adenomatoid odontogenic tumor with unusual presentation extending from gingiva to periodontal space. Issue 6 (November 2018) - Saito, Anna; Taguchi, Akira; Hasegawa, Hiromasa; Kagami, Hideaki
Abstract: Adenomatoid odontogenic tumor is a relatively rare tumor that typically occurs at the anterior part of the maxilla. Most cases arise as a central or intraosseous tumor accompanying an impacted tooth; thus, the radiological appearance resembles that of an odontogenic cyst. The tumor is divided into three subtypes depending on its location and relationship with the impacted tooth: the central variant associated with the crown of an unerupted tooth (follicular type); the central variant with no association with the crown of an unerupted tooth (extrafollicular type); and the peripheral (gingival) variant. Among them, the occurrence of peripheral variant is reportedly very rare, and they usually exhibit an epulis-like or fibroma-like appearance. This paper reports an unusual case of adenomatoid odontogenic tumor. Remarkably, the tumor extended into the buccal periodontal space, expanding the space possibly due to tumor growth without relevant absorption of labial alveolar bone. The adjacent gingiva looked normal except for the slight swelling. On histopathological analysis, the tumor showed no direct connection to the periodontal ligament, which may indicate the possible origin of this tumor as an epithelial remnant of the dental lamina in the peripheral gingiva.